In vitro susceptibility of 90 penicillin-susceptible and -resistant pneumococci to penicillin G, amoxicillin, amoxicillin/clavulanate, cefaclor, cefuroxime, cefpodoxime, cefixime and imipenem - Hupková, H; Trupl, J (Folia microbiologica, 1998)
In vitro susceptibility of eight antibiotics was compared using three groups of pneumococci and agar dilution method comprising 30 penicillin-susceptible, 30 intermediately penicillin-resistant, and 30 highly penicillin-resistant pneumococci. Decreased sensitivity to all beta-lactam agents of intermediately penicillin-resistant and highly penicillin-resistant pneumococci is shown. MIC50 and MIC90 was lower with amoxicillin with and without clavulanate by one dilution than with penicillin. Cephalosporin MIC90s were all significantly higher for intermediately resistant and fully resistant strains. Only imipenem was more active than penicillin with MIC90 of susceptible pneumococci 0.015 mg/L, intermediately resistant pneumococci 0.25 mg/L, resistant pneumococci 1 mg/L.
Keywords: Microbial Sensitivity Tests; laktamy; Humans; pneumokokové infekce; Penicillin Resistance; Penicillins; mikrobiální testy citlivosti; lidé; antibakteriální látky; Lactams; Cephalosporins; Pneumococcal Infections; Penicillin G; Anti-Bacterial Agents; penicilin G; peniciliny; Streptococcus pneumoniae; rezistence na penicilin; cefalosporiny